Eastern European Perspectives on the Restitution of Nazi-Looted Jewish Cultural Property : Gershom Scholem in Prague, 1946 - Holzer-Kawalko, Anna (Naharaim, 2022)
This article offers a critical examination of the travel diaries written by Gershom Scholem (1897-1982), a well-known pioneer scholar of Jewish mysticism and a professor at the Hebrew University of Jerusalem. In 1946, Scholem was sent to Prague on behalf of the Hebrew University to retrieve the Nazi-looted Jewish libraries from Czechoslovakia to Palestine. In recent years, at the same time as a significant rise of scholarly interest in the fate of the plundered Jewish books and manuscripts, Scholem's accounts have come to serve as a main source of information on the Jewish cultural property in the Bohemian lands. Where most of the currently available studies take his description of the Czechoslovak restitution affairs almost for granted, this article seeks to adopt a more distant approach to these materials, by undertaking a comparison with the documentation produced by the local Jewish bodies and the archival sources of the Czechoslovak authorities responsible for the management of Jewish assets. Zooming in on the encounter between Scholem and the leaders of the Jewish community in Prague, the paper points especially to the multiple misunderstandings that arose between the two parties during his visit. It then explores the difference between his and the Prague protagonists’ perspectives on the Nazi-looted Jewish cultural property.